Longitudinal evaluation of Tau‐P301L transgenic mice reveals no cognitive impairments at 17 months of age. Issue 1 (18th December 2017) - Kent, Brianne A.; Heath, Christopher J.; Kim, Chi Hun; Ahrens, Rosemary; Fraser, Paul E.; St George‐Hyslop, Peter; Bussey, Timothy J.; Saksida, Lisa M.
Abstract: Introduction: Tau is a microtubule‐associated binding protein implicated in neurodegenerative tauopathies, including frontotemporal dementia (FTD) and Alzheimer's disease (AD). These diseases result in the intracellular accumulation of hyperphosphorylated tau in the form of neurofibrillary tangles, the presence of which is associated with cognitive deficits. Methods: We conducted a longitudinal behavioral study to provide a profile of the TgTau(P301L)23027 transgenic mouse in multiple cognitive domains across multiple ages. P301L is the tau mutation most frequently observed in patients with frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP‐17) and this mouse model recapitulates the progressive development of glial and neurofibrillary tangles, and associated cerebral atrophy observed in patients. We examined frontal cortex‐dependent executive function and attention with the touchscreen 5‐choice serial reaction time test (5‐CSRTT) and assessed the function of temporal cortical structures using novel object recognition (OR). Results: Despite using sensitive tasks, there were no apparent changes in executive function, attention, or recognition memory in the transgenic mice from 5 to 17 months of age. Conclusions: This study represents the first comprehensive longitudinal analysis of cognition in the TgTau P301L mouse model and suggests that this model is not ideal for studying early attention and recognition memory impairments associated with tauopathy. However, spatial and object recognition memory impairments were observed during follow‐up assessments when the mice were 18 and 21 months, respectively. These impairments are consistent with previous publications, and with a dementia‐like phenotype in these mice when aged. Abstract : Tau is a microtubule‐associated binding protein implicated in neurodegenerative tauopathies, including frontotemporal dementia (FTD) and Alzheimer's disease (AD). This study is the first comprehensive longitudinal analysis of cognition in the TgTauP301L mouse model and suggests that this model is not ideal for studying early attention and recognition memory impairments associated with tauopathy.